Enhancing Retail Performance through Customer Traffic Analysis and Personalized Marketing Strategies: A Systematic Approach - Sucharan Jandhyala (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article comprehensively examines how implementing advanced customer tracking systems and targeted marketing strategies can transform retail business performance. The article investigates the integration of cutting-edge counting systems, purchase tracking mechanisms, and personalized marketing approaches to enhance retail operations and customer engagement. The research demonstrates the effectiveness of a systematic approach to retail optimization through detailed analysis of traffic patterns, purchase behaviors, and customer responses to targeted marketing initiatives. The article encompasses sophisticated data collection protocols, advanced analytical frameworks, and carefully designed implementation strategies considering technical requirements and privacy concerns. The findings reveal significant improvements in key performance metrics, including traffic conversion rates, category-specific sales performance, and marketing response rates. The article also explores the business impact through revenue growth projections, customer loyalty measurements, and return on marketing investment analyses. This article provides valuable insights for retail practitioners seeking to enhance their operations through data-driven decision-making and offers a framework for implementing comprehensive customer tracking and marketing systems. The findings suggest that such integrated approaches are becoming increasingly crucial for maintaining competitiveness in the modern retail environment while emphasizing the importance of balancing technological advancement with customer privacy and ethical considerations.